Effective Use of Performance-based Assessments to Identify English Knowledge and Skills of EFL Students in Ecuador - Espinosa Cevallos, Ligia F. (2015)
This paper seeks to understand how EFL teachers can effectively use performance-based assessments to determine the English knowledge and skills that EFL students have developed during the teaching-learning process. It also presents the advantages of this type of assessment as well as its challenges and the way these challenges can be overcome. Through this investigation, EFL teachers in Ecuador and around the world will be able to get valuable information that will guide their assessment practices in EFL classrooms.